Efek Anti Konstipasi Bakso Ikan Lele Dengan Penambahan Rumput Laut (Eucheuma Cotonii) Terhadap Tikus Jantan Galur Wistar (Rattus Novergicus) Yang Diinduksi Gambir - Pinky Natalia Samanta; I Made Sugitha; I Putu Suparthana (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology), 2018)
The pertinence of dietary fiber to decrease the transit time intestinal and increase the mass of feces makes it can be used as laxative for prevent constipation. This research is in purpose to know the ability of catfish meatballs which have been added flour seaweed. There are two stages for this reserch. The first stage is to get the best consentration of a high dietary catfish meatballs. Second stage is in vivo testing of the rats by giving the best dosage of meatballs 2 g, 4 g, 6 g, 8 g. Statistical analysis on One Way Anova showed there is no real difference infulence by giving four dosages to defecation frequency and feces consistency. Once giving the greater dosage, so the feces weight and defecation frequency will be greater also. 2 g/200 g dosage of the rats weight will be able to put rats feces back become normal by rats defecate frequency in 21 times a day and feces water content 47,93%.